Associations between statin use and negative affective bias during COVID-19: an observational, longitudinal UK study investigating depression vulnerability - Gillespie, AL; Wigg, C; Van Assche, I; Murphy, SE; Harmer, CJ (Elsevier, 2022)
Background There is growing interest in the antidepressant potential of statins. We tested whether statin use is associated with cognitive markers previously found to indicate psychological vulnerability to depression within the context of the COVID-19 pandemic. Methods Between April 2020 and February 2021, we conducted an observational online study of 2043 adults in the United Kingdom. Participants completed cognitive tasks assessing processes related to depression vulnerability, including affective bias and reward processing. We also measured working memory, medication use, and current psychiatric symptoms. Using mixed analysis of covariance and regression models, we compared participants on statins alone (n = 81), antihypertensive medication alone (n = 126), both medications (n = 111), and on neither medication (n = 1725). Results Statin use was associated with reduced recognition of angry and fearful faces (F1 = 9.19, p = .002; F1 = 6.9, p = .009) and with increased misclassification of these expressions as positive. Increased recognition of angry faces at baseline predicted increased levels of depression and anxiety 10 months later (β = 3.61, p = .027; β = 2.37, p = .002). Statin use was also associated with reduced learning about stimuli associated with loss (F1,1418 = 9.90, p = .002). These indicators of reduced negative bias were not seen in participants taking antihypertensive medication alone, suggesting that they were related to statin use in particular rather than nonspecific demographic factors. In addition, we found no evidence of an association between statin use and impairment in working memory. Conclusions Statin use was associated with cognitive markers indicative of reduced psychological vulnerability to depression, supporting their potential use as a prophylactic treatment for depression.